2020
DOI: 10.1002/lary.29188
|View full text |Cite
|
Sign up to set email alerts
|

A National Evaluation of Food Insecurity in a Head and Neck Cancer Population

Abstract: Objectives/Hypothesis To determine the food security status of patients with a history of head and neck cancer and compare to other types of cancer. Study Deign A retrospective analysis using the National Health Interview Series. Methods The National Health Interview Series (NHIS) for the calendar years 2014 to 18 was used to elicit food security status (secure, marginally secure/not secure) among adult patients with a history of throat/pharynx head and neck cancer (pHNC), thyroid cancer, and colon cancer. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…While improvement in overall nutritional health has proven to be an important achievement of public health efforts to promote healthy dietary patterns and prevent chronic diseases and cancers, disparities continue to persist among various populations, including rural or geographically isolated, and ethnic minorities [ 66 , 67 ]. A recent study found that patients with a history of throat cancer are more likely to live in areas with food insecurity, especially among Black and Hispanic groups [ 68 ]. Increasing screenings for food insecurity among patients with HNC, especially among patients from disadvantaged groups, is needed to improve equal access to care, which can be further exacerbated by socioeconomic status, income, race and ethnicity, and geographical residence [ 66 ].…”
Section: Nutritionmentioning
confidence: 99%
“…While improvement in overall nutritional health has proven to be an important achievement of public health efforts to promote healthy dietary patterns and prevent chronic diseases and cancers, disparities continue to persist among various populations, including rural or geographically isolated, and ethnic minorities [ 66 , 67 ]. A recent study found that patients with a history of throat cancer are more likely to live in areas with food insecurity, especially among Black and Hispanic groups [ 68 ]. Increasing screenings for food insecurity among patients with HNC, especially among patients from disadvantaged groups, is needed to improve equal access to care, which can be further exacerbated by socioeconomic status, income, race and ethnicity, and geographical residence [ 66 ].…”
Section: Nutritionmentioning
confidence: 99%